Concert „Transoceanic Encounters: Brazil-Mozambique“ with Alexandre Vieira and Luka Mukhavele (Readings, Concerts and other events, 2023)
In June 2023 the Africa Multiple Cluster of Excellence presented a concert featuring the musician Alexandre Vieira from Brazil visiting Bayreuth for an artist fellowship and Mozambiquan musician Luka Mukhavele. Luka Mukhavele Luka Mukhavele is a music/Culture scholar, artist, instrument builder, and language teacher, from Mozambique. He engaged with music from early age, influenced by family members and community, which were very musical. Since buying toys for children was no a common practice, Luka and his friends taught themselves to build their own, and this included musical instruments. In 2005, Luka founded Mukhambira-musical, to research on the construction and performance of African musical. Adding to Mukhambira, Luka's PhD thesis “African Musical Instruments from a Contemporary Global Perspective —Mbira and Xizambi”, competed at Hochschule für Musik Franz Liszt Weimar, emerged as his artistic-academic approach to the reinvigoration African music and instruments and their integration in the global body of artistic and scientific knowledge in musicology, a discipline which he finds to have many ideological, conceptual, and paradigmatic detriments. Currently, Luka is the Editor/Designer of the course “Living Heritage in Africa: Music and the Performing Arts”, a freelancer consultant, artist, and lecturer. Both his artistic and his academic work are grounded on his “African Contemporary self-built instruments, from which he draws otherwise lost concepts and paradigms, aiming to address the shortfalls and inherent detriments of musicology in a global perspective. Alexandre Vieira Alexandre Vieira is a Brazilian musician based in Salvador - Bahia - Brasil. Master in music performance - Universidade Federal da Bahia (UFBA), plays upright bass, electric bass, guitar, percussion and sing, performing as a frontman and sideman. Born in a musical family, started playing in his early childhood with his father, sister and brother, became professional at 17 years old. Played and recorded alongside great artists from Brazil and abroad. His most recent and representative participations include the series of concerts Isso Ainda Dá Repercussão based on the work of the Brazilian composer Itamar Assumpção, the project Chulas na Feira at Santo Amaro da Purificação with Roberto Mendes, the recording of the album Fogueira Doce by MateusAleluia (Os Tincoãs), the recording of the album Afrodiaspórico by Luan Sodré Trio, the recording of the EP Grito by Manuela Rodrigues, collaborating as a musician for the Whale Whispering project by Michaela Harrison, and most recently the recording of the album Dança do Tempo by Ubiratan Marques and Asé Ensemble which will be fully released in 2023. Self-taught on most instruments, started playing upright bass at the university playing both classical and jazz, from where he aroused his interest to delve into Afrodiasporic arts, exploring the creative processes that involve oralities and corporeities connected with musical instruments.